Analisa Yuridis Tentang Tindak Pidana Korupsi Yang Menyebabkan Kerugian Negara Dalam Prespektif Putusan Mahkamah Konstitusi Republik Indonesia - Achmad Mahendra; Ramlani Lina Sinaulan; Tofik Yanuar Chandra (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The Constitutional Court believes that the element of state loss must be established and quantified, even if it is an estimate or has not yet occurred. Corruption is defined in detail in 13 articles of Law No. 31 of 1999, as revised by Law No. 20 of 2001 on the Eradication of Corruption Crimes. Corruption is classified into 30 distinct forms/types in these articles. These articles discuss the types of conduct that may result in criminal sanctions as a result of corruption. Indonesia is a constitutional monarchy. This is established in Article 1 paragraph three of the 1945 Constitution, which states that the State of Indonesia is a state of law. Indonesia's state of the law is one that always evaluates all activities on two bases. That is, in terms of its intended use or purpose and its legal foundation. The author employs a descriptive qualitative methodology in this paper. This study takes a normative juridical approach as well as a statutory or juridical method, namely legal product research.